EFFECTIVENESS OF MEDICAL STUDENT COUNSELING FOR HOSPITALIZED PATIENTS ADDICTED TO TOBACCO (MS-CHAT): A RANDOMIZED CONTROLLED TRIAL - Priyanka Satish; Aditya Khetan; Dharav Shah; Prathisha Vinoth; Amina Shahala AP; Aiswarya Raj; Shreya Cherian; Faiez Farhan; Priyanka Gangadharan; GR Nivashini; V Nanthini; Rohan Thommen; et al. (Elsevier, 2023)
Disclosures: A. Khetan is a co-founder of SEHAT (Society to Enhance Health and Access to Treatments), Dalkhola, West Bengal, India. SEHAT provided funding for this study. Other authors have no relevant financial disclosures. Therapeutic Area: ASCVD/CVD Risk Factors; Preventive Cardiology Best Practices Background: The need for, and effectiveness of physician counseling for tobacco has been well emphasized. However, the medical curriculum in many countries offers very little training needed to offer effective behavioral counseling. We hypothesized that providing medical students with experiential training in tobacco cessation counseling will improve their knowledge, while providing a valuable resource to help patients quit. Methods: pandemic, the primary outcome was changed from a biochemically verified quit rate to self-reported 7-day point prevalence of smoking cessation at 6 months. Changes in medical student knowledge were assessed using a pre- and post-questionnaire delivered prior to and 12 months after training. Results: Among 688 patients randomized across three medical schools, 343 were assigned to the intervention group and 345 to the control group. After 6 months of follow up, the primary outcome occurred in 188 patients (54.8%) in the intervention group, and 145 patients (42.0%) in the control group (absolute difference 12.8%; relative risk, 1.67; 95% confidence interval, 1.24-2.26; p <0.001). Among 70 medical students who participated in the study, knowledge increased from a mean score of 14.8 (±0.8, maximum score of 25) at baseline to a score of 18.1 (±0.8) at 12 months, an absolute mean difference of 3.3 (95% CI, 2.3-4.3; p <0.001). Conclusion: This is an effective, low cost intervention that achieves the dual purpose of providing experiential training in behavioral counseling to future physicians, while simultaneously helping tobacco users quit. It is easily scalable and can be tailored to meet the needs of medical education and tobacco cessation programs in health systems across the world.